2019
DOI: 10.4025/actasciagron.v41i1.42620
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations and ecological risk assessment of the suspended sediments of a multi-contaminated Brazilian watershed

Abstract: Metal concentrations in suspended sediments of one of the most polluted rivers in Brazil were measured. Concentrations of Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn were determined by inductively coupled plasma while Hg and As were analyzed with hydride generation flow injection atomic absorption spectroscopy. Contamination of As, Cd, Cr, Cu, Fe, Hg, Mn, Ni, Pb, and Zn was assessed using pollution indices, ecological risk assessment, statistical multivariate techniques and comparison with sediment quality guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
2
12
1
Order By: Relevance
“…When EF values exceed 20, sediments are considered significantly enriched with metals. Such high EF values are usually associated with anthropogenic inputs [65]. The computed EF values in the present study indicate that the sediments were very highly to extremely enriched with respect to As and Cd regardless of sampling site and sampling period (Fig.…”
Section: Enrichment Factor Efsupporting
confidence: 55%
“…When EF values exceed 20, sediments are considered significantly enriched with metals. Such high EF values are usually associated with anthropogenic inputs [65]. The computed EF values in the present study indicate that the sediments were very highly to extremely enriched with respect to As and Cd regardless of sampling site and sampling period (Fig.…”
Section: Enrichment Factor Efsupporting
confidence: 55%
“…For sediments, it was observed that the concentrations of Pb, Zn, Cd and Cu from the Nasivi river were lower than the respective concentrations reported for the Suva Harbor in Fiji (Maata and Singh, 2008). While metal concentrations from this study were far below those reported for the Molonglo river in Australia (Marasinghe Wadige et al, 2016), they exceeded those reported for the Ipojuca river in Brazil (Silva et al, 2019)and the Jequetepeque River Basin in Peru (Yacoub et al, 2012).…”
Section: Heavy Metal Concentrations In Farm Soils and River Sedimentscontrasting
confidence: 78%
“…The minimal mean contents are those in the Tinto River (Spain) which are of a point character and are due to a sulfide deposit operating in the vicinity of city of Narva (Morillo et al, 2002). In the Hrazdan River mean contents of Mn make 747mg/kg, which is very close to the values registered in bottom sediments of the Ipojuca (Da Silva et al, 2019). For the Hrazdan and the Ipojuca, no pronounced manganese pollution sources have been identified; in both cases, such contents of this element result from a discharge of untreated urban domestic waters into the rivers.…”
Section: 2supporting
confidence: 49%
“…The Guadaira River (Spain) stands out by the minimal contents of elements and specifically arsenic, the only cause of which is the former olive processing workshop. The sampling locations are not currently exposed to anthropogenic impacts (Enguix González et al, 2000) In the bottom sediments of the Hrazdan River, mean contents of arsenic are similar to those in the Ipojuca River (Brazil) which flows through heavily populated settlements, where similarly to Yerevan, no pronounced arsenic pollution sources are found either (Da Silva et al, 2019).…”
Section: 2mentioning
confidence: 91%
See 1 more Smart Citation